Investigating the relationship between organizational health and social responsibility of administrative staff of Rafsanjan University of Medical Sciences - Fatemeh Rokh-Forouz; Zahra Rokh-Forouz; Maryam HASHEMIAN; Mostafa NASIRZADEH (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: Social responsibility is critical to the success of organizations and is a key factor in any organization's survival. In this regard, the present study was conducted to investigate the impact of the relationship between organizational health and social responsibility in administrative staff of Rafsanjan University of Medical Sciences.  Methods: This research is a descriptive correlation study. The statistical population of this study consisted of all the administrative staff of Rafsanjan University of Medical Sciences in the year 2018 that 139 persons were selected by censusmethod. Data collection tools included standard questionnaires of organizational health and social responsibility. The collected data were analyzed by SPSS-16 software using Pearson correlation, independent t-test and one-way ANOVA. Results: The findings show that in this organization social responsibility with average of 127/89 ±17/91 and organizational health with mean of 149/15 ± 23/36 are both at relatively high level and organizational health has a direct and significant correlation with social responsibility of employees (P= 0/01, r= 0/21). Conclusions: The healthy atmosphere of an organization affects the attitude, performance and belief level of employees, which makes them more committed and responsible and ultimately leads to the growth and development of the organization. In the present study, organizational health has been one of the main determinants of the level of social responsibility of employees that changes in its level affect social responsibility. Therefore, the managers of the organization concerned with proper planning can promote the social responsibility of the employees and finally provide the performance of organizations.